Perception by neighbors of the forest rehabilitation in the protection zone of the Pirro river - Villalobos, Ronny (2013)
The increase in urban sprawl and all its economic and productive activities exert pressure on the environment of areas aimed to the protection and conservation of water resources. Therefore, the study of the perception of inhabitants on the banks of rivers results key among decision makers, in order to reduce the impacts that humans exerted toward the environment on these urban ecosystems. Special attention is given to aspects of current and future land use in the buffer zone of the Pirro river, in the province of Heredia, Costa Rica; likewise the perception of inhabitants concerning the participation of local governments and other institutions is analyzed.